Adolescentna medicina: 3. in 4. modul (University of Maribor Press, 2024)
Adolescet medicine: 3. and 4. Module. In the third and fourth modules of Adolescent Medicine we summarized current contents which are important for physicians and other health professionals who during their work encounter adolescents and young adults. Successful integration and appropriate usage of health care system are among key factors for healthy development of adolescents. For this reason health care literacy is an important task of health care workers, health care system and the entire society. Knowledge of ethical and legal aspects of rights and responsibilities of adolescents and parents significantly contributes to safe medical treatment. Searching for gender identity and care of sexual health represent a special challenge for adolescents. Aware health professionals may, with appropriate preventive action and appropriate approach, significantly relieve adolescents of distress connected with sexual development and sexual life. Various forms of violence among young people and chemical and non-chemical addictions are a current social phenomenon. In the textbook the mechanisms, causes, consequences and various approaches to treatment and reducing the burden of addiction and violence among adolescents are represented. Preventive health care for children and adolescents has a rich tradition in Slovenia and excellent results. The organization of preventive health care for school children and adolescents and students are represented. To the readers of our publication we wish successful work with young people.